Psychometric properties of the Persian version of the New Sexual Satisfaction Scale (NSSS) - Shakib , Niloufar; Kachooei , Mohsen; Fathi-Ashtiani , Ali (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to investigate the psychometric properties of the Persian version of the New Sexual Satisfaction Scale (NSSS). Methods: The research was descriptive. The statistical population included all married men and women who referred to counseling centers in Tehran's second district. Six centers were selected by simple random sampling and 295 people (171 females and 124 males) were selected by convenience sampling method. The instrument used was the New Sexual Satisfaction Scale. Confirmatory factor analysis and Cronbach's alpha reliability and retest coefficient were used to evaluate the validity of the scale structure. Data were analyzed using LISREL and SPSS software. Results: The results showed that the new sexual satisfaction scale in the first-order factor structure was confirmed using confirmatory factor analysis. The retest coefficient obtained from the test was estimated at one week intervals. The Cronbach's alpha coefficient of the whole scale is 0.85 and its retest coefficient is 0.80. Conclusion: It can be concluded that the Persian version of the New Sexual Satisfaction Scale (NSSS) has good validity and reliability and is an effective self-report tool for research purposes and couples counseling.